Resting-State Functional Connectivity Differences Following Experimental Manipulation of the Orbitofrontal Cortex in Two Directions via Theta-Burst Stimulation. (January 2023) - Price, Rebecca B.; Ferrarelli, Fabio; Hanlon, Colleen; Gillan, Claire M.; Kim, Tae; Siegle, Greg J.; Wallace, Meredith L.; Renard, Marlee; Kaskie, Rachel; Degutis, Michelle; Wears, Anna; Brown, Vanessa; et al.
Compulsive behaviors (CBs) have been linked to orbitofrontal cortex (OFC) function in animal and human studies. However, brain regions function not in isolation but as components of widely distributed brain networks—such as those indexed via resting-state functional connectivity (RSFC). Sixty-nine individuals with CB disorders were randomized to receive a single session of neuromodulation targeting the left OFC—intermittent theta-burst stimulation (iTBS) or continuous TBS (cTBS)—followed immediately by computer-based behavioral "habit override" training. OFC seeds were used to quantify RSFC following iTBS and following cTBS. Relative to cTBS, iTBS showed increased RSFC between right OFC (Brodmann's area 47) and other areas, including dorsomedial prefrontal cortex (dmPFC), occipital cortex, and a priori dorsal and ventral striatal regions. RSFC connectivity effects were correlated with OFC/frontopolar target engagement and with subjective difficulty during habit-override training. Findings help reveal neural network-level impacts of neuromodulation paired with a specific behavioral context, informing mechanistic intervention development.